Trophic Factors from Tissue Stem Cells for Renal Regeneration - Kenji Tsuji; Shinji Kitamura (Stem Cells International)
Stem cell therapies against renal injury have been advancing. The many trials for renal regeneration are reported to be effective in many kinds of renal injury models. Regarding the therapeutic mechanism, it is believed that stem cells contribute to make regeneration via not only direct stem cell differentiation in the injured space but also indirect effect via secreted factors from stem cells. Direct differentiation from stem cells to renal composed cells has been reported. They differentiate to renal composed cells and make functions. However, regarding renal regeneration, stem cells are discussed to secrete many kinds of growth factors, cytokines, and chemokines in paracrine or autocrine manner, which protect against renal injury, too. In addition, it is reported that stem cells have the ability to communicate with nearby cells via microvesicle-related RNA and proteins. Taken together from many reports, many secreted factors from stem cells were needed for renal regeneration orchestrally with harmony. In this review, we focused on the effects and insights of stem cells and regenerative factors from stem cells.